FREGE ON INFORMATIVE IDENTITIES BETWEEN STATEMENTS (Revista Română de filosofie analitică, 2025)
The Frege-Husserl correspondence can be fruitfully explored so as to provide new insight into the paradox of analysis. Why are some identifies informative and others not? And how could we ascertain the issue if under scrutiny are mathematical identities, necessarily true if true at all? This text articulates the distinction between logical and semantic criteria in order to clarify a possible Fregean solution to the paradox of analysis, starting from regarding analysis as generating particular cases of Frege puzzles.